OBESITY, INFLAMMATION AND HFpEF – PARTS OF THE SAME CIRCULUS VITIOSUS - Milisavljević, Katarina; Petrović, Aleksandra; Jelić , Filip; Zdravković, Dimitrije; Zdravković, Marija (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Heart failure with preserved ejection fraction (HFpEF) accounts for more than half of chronic heart failure cases, and obesity is among its most common comorbidities, which has reached epidemic proportions and is associated with the progressive deterioration of HFpEF. Oxidative stress and systemic inflammation, largely driven by visceral adipose tissue, promote endothelial dysfunction, coronary microvascular injury, myocardial remodeling and stiffness through fibrosis, the key pathophysiological mechanisms in HFpEF. This review paper aims to summarize current evidence on the epidemiological association between obesity and HFpEF, as well as the pathophysiological mechanisms linking these conditions. It also presents clinical and experimental findings demonstrating that obesity, HFpEF, and inflammation constitute interconnected components of one and the same circulus vitiosus.Methods: This review draws upon relevant literature and clinical research retrieved from the PubMed, NCBI, and ResearchGate databases, focusing primarily on the underlying pathophysiological mechanisms and evidence derived from clinical trials. Particular emphasis was placed on modern weight-management pharmacotherapies (SGLT2 inhibitors, GLP-1 receptor agonists) and management of major comorbidities (DM, AHT, OSA, and NAFLD), with the aim of reducing the considerable burden of morbidity and mortality in this growing patient population.Results: Better understanding of the interacting mechanisms in obesity and HFpEF supports development of therapeutic strategies such as dual GLP-1/GIP agonists and anti-cytokine approaches aimed at reducing systemic inflammation and the risk of HFpEF worsening, with potential improvements in functional capacity and quality of life.Conclusion: Obesity is a major comorbidity in HFpEF, with inflammation playing a central role in pathogenesis. Targeted anti-inflammatory and metabolic therapies show potential to reduce morbidity and mortality and enable a more individualized treatment approach.
Keywords: visceral adiposity; diastolic dysfunction; endothelial dysfunction; myocardial fibrosis; SGLT2 inhibitors; GLP-1/GIP agonists